Numerical Modification of Piping Systems to Increase Flow Velocity in Receiving Facilities - Rinaldi; weriono, weriono; Adi Isra; Ajar Darmawan (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2024)
The process of unloading avtur via bridger capacity of 24 KL through the piping system at the DPPU SSK II receiving facility takes 55-60 minutes with an average unloading flow rate is 27 m3/hour while the pump flow rate specification used is 60 m3/hour. In the process of unloading avtur through a piping system, there are various kinds of fitting. Where in the operation of the piping system can result losses caused by pipe roughness, pipe length, flow capacity, and components installed in the system. This study aims to determine the total head, minor and major losses of the piping system using the Darcy-Weisbach equation in mathematical calculation methods and simulations in the pipe flow expert software, the result of simulations will be compared with mathematical calculations to modify the piping system so can be obtained for increasing the flow rate of fluid flow to speed up the unloading process of avtur via bridger. The results of this study are: 1.) The total head value of the receiving piping system using the calculation method is 16.51 m while using a flow expert simulation is 12.9 m. 2.) The results of mathematical calculations of the energy equation for the piping system at the receiving facility obtained a flow rate of 55.2 m3/hour. 3.) From the results of system modifications by increasing the flow rate capacity to 80 m3 / hour and the pump head achieved 16.05 m, According to the simulation results of the software flow expert, pumping flow rate increase of 72 m3/ hour.